Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1600-0560.2010.01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of cutaneous sporotrichosis in Rio de Janeiro: a series of 119 consecutive cases

Abstract: The histopathological characteristics of sporotrichosis were variable when the causative fungus was not seen. In a proper context, the diagnosis of sporotrichosis remains a potential consideration even in the absence of demonstrable yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 16 publications
(34 reference statements)
2
53
0
1
Order By: Relevance
“…When the fungus is not in evidence, suppurative granulomas, neutrophils, and liquefaction necrosis are uncommon (187).…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…When the fungus is not in evidence, suppurative granulomas, neutrophils, and liquefaction necrosis are uncommon (187).…”
Section: Histopathological Examinationmentioning
confidence: 99%
“…Splendore first observed this structure in 1908 on tissue sections from patients with sporotrichosis and afterwards by Hoeppli in 1932 around schistosome larvae (Kwon-Chung & Bennett, 1992). Positive identification of this structure in tissue sections from patients with sporotrichosis ranges from 20% to 66% (Gezuele & Rosa, 2005); although other authors reported that this structure was not observed in several analysed samples (Quintella et al, 2011). These histopathologic findings help to differentiate sporotrichosis from other diseases.…”
Section: Conventional Diagnosismentioning
confidence: 92%
“…The presence or predominance of epithelioid granulomas, caseous/fibrinoid necrosis and fibrosis as well as the occurrence of foreign body granulomas with predominance of lymphocytes is related to a lack of fungal observation. Suppurative granulomas, neutrophils and liquefaction are more common when S. schenckii yeast-like cells are encountered (Quintella et al, 2011). Several authors observed the Splendore-Hoeppli reaction on histopathologic tissue sections from sporotrichosis patients.…”
Section: Conventional Diagnosismentioning
confidence: 95%
See 2 more Smart Citations